PENGARUH VARIASI KECEPATAN PEMOTONGAN DAN TEKANAN OKSIGEN MESIN FIBER LASER CUTTING TERHADAP KEKASARAN PERMUKAAN DARI MATERIAL STAINLESS STEEL 304: EFFECT VARIATION CUTTING SPEED AND OXYGEN PRESSURE OF FIBER LASER CUTTING MACHINE ON SURFACE ROUGHNESS OF 304 STAINLESS STEEL MATERIAL - Mohammad Rudi Romadhoni; Samsul Hadi (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2024)
Industrial development in Indonesia is currently taking place very rapidly, one of the industrial sectors that has an important role in increasing Indonesia's development is the manufacturing industry. Pahala Workshop is a service workshop engaged in the manufacturing industry that offers plate cutting services using a fiber laser cutting machine. The fiber laser cutting machine in Pahala Workshop is quite new and is starting to be in demand by many customers. For different types of materials, there are different cutting standards and parameters. The purpose of the study was to determine the effect of variations in cutting speed and oxygen pressure of fiber laser cutting machines on the surface roughness of 304 stainless steel material so as to determine the optimal parameters for the cutting process. The research method used a real experiment method with the independent variables of cutting speed (1400, 1700 and 2000 mm/min) and oxygen pressure (3, 4, 5, 6 and 7 Bar) and the dependent variable of surface roughness. The results showed that the lowest average value of surface roughness (Ra) of 5.087 µm was obtained at a cutting speed of 1400 mm/min and oxygen pressure of 7 Bar. While the highest average value of surface roughness (Ra) is 8.604 µm obtained at a cutting speed of 2000 mm/min and oxygen pressure of 3 Bar. Cutting speed and oxygen pressure affect surface roughness. The effect of cutting speed on the surface roughness value is that the faster the cutting speed, the shorter the cutting time so that the laser heat energy that hits the work plane area is not maximized. While the effect of auxiliary gas pressure (oxygen) on fiber laser cutting machine that hits the work plane area is getting uneven as the cutting speed increases.